Development and future of ultraviolet light-emitting diodes: UV-LED will replace the UV lamp - Muramoto, Yoshihiko; Kimura, Masahiro; Nouda, Suguru (Semiconductor science and technology, 2014)
Ultraviolet light-emitting diodes (UV-LEDs) have started replacing UV lamps. The power per LED of high-power LED products has reached 12 W (14 A), which is 100 times the values observed ten years ago. In addition, the cost of these high-power LEDs has been decreasing. In this study, we attempt to understand the technologies and potential of UV-LEDs.